A graph of dark energy significance on different spatial and mass scales - Teerikorpi P; Heinamaki P; Nurmi P; Chernin AD; Einasto M; Valtonen M; Byrd G (EDP SCIENCES S A, 2022)
Conclusions. The log <rho(m)>/rho(Lambda) vs. log R diagram is a useful and versatile way to characterize the dynamical state of systems of galaxies within the Lambda-dominated expanding universe.</rho(m)>